Plants, power, possibility: maneuvering the medical landscape in response to chronic illness and uncertainty - Kelly, T (2014)
This thesis is concerned with plants, chronic illness and medicine in Oku, Northwest Region, Cameroon. I focus on patient strategies to obtain effective medical outcomes, and on how such outcomes may be obtained through seeking traditional medicine in Oku. I argue that biomedical notions of efficacy do not appropriately represent the central and diverse roles that plants play in traditional medicine nor do they correctly represent how people in Oku evaluate the efficacy of plant-based traditional medicine. I argue instead that efficacy must be understood in terms of the emic concept of power. This power is understood to be located in the Oku landscape, which is still uniquely forested and said to embody powerful ancestral spirits. With plants as the primary tangible material of power, and traditional doctors in Oku as those who claim exclusive rights to manipulate and disperse such power, I discuss traditional medicine in Oku as a system wherein power from the natural landscape is drawn upon to challenge harmful powers feared to derive from the social arena. Using the pragmatic and phenomenological approaches, I show how patients evaluate the efficacy of a medical treatment based on their bodily experiences, and how their actions, as revealed in their therapeutic trajectories, reveal their satisfaction or dissatisfaction with a given diagnosis and/or therapy. I discuss how enduring illness generates and exacerbates bodily, treatment-outcome, social, and psychological uncertainties. In this context, effective outcomes can be understood as those which address and limit these uncertainties and anxieties while offering ways to imagine hopeful prognoses. This thesis then outlines the major sources of uncertainty, people’s responses to such uncertainties, and what people might achieve in terms of limiting uncertainties by seeking traditional medicine in Oku.